Two-degree-of-freedom modal response history analysis of buildings with specific vertical irregularities. (1st April 2019) - Lin, Jui-Liang; Tsaur, Chih-Chia; Tsai, Keh-Chyuan
Highlights: A simplified analysis method for buildings with specific vertical irregularities. Two-degree-of-freedom modal systems are developed for the specific buildings. The drastic change in the peak inter-story drifts of the buildings is captured. Abstract: Vertically irregular buildings with strong or stiff-and-strong lower stories such as setback buildings are common in engineering practice. However, besides a sophisticated nonlinear response history analysis, there seems to be no simplified seismic analysis method suitable for this type of building. Thus, this study explores a two-degree-of-freedom (2DOF) modal system for representing each vibration mode of such buildings. The upper and lower degrees of the 2DOF modal system respectively simulate the modal responses of the two distinct parts ( i.e., the upper stories and the lower stories) of a building with strong or stiff-and-strong lower stories. Instead of a conventional single degree-of-freedom modal system, the 2DOF modal system is employed in the modal response history analysis of buildings with the specific vertical irregularities. The effectiveness of the proposed seismic analysis method is verified by investigating four 9-story and four 20-story buildings, which have the lower stories stronger or stiffer-and-stronger than the upper stories. Each of the eight example buildings is subjected to three ensembles of ground motion records.